EFEKTIFITAS ULTRASOUND DIATHERMY DAN MUSCLE ENERGY TECHNIQUE DENGAN TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN MUSCLE ENERGY TECHNIQUE TERHADAP KEMAMPUAN FUNGSIONAL PASIEN OSTEOARTHRITIS GENU : PERBANDINGAN MUSCLE ENERGY TECHNIQUE DAN ULTRASOUND DIATHERMY DENGAN MUSCLE ENERGY DAN TENS TERHADAP KEMAMPUAN FUNGSIONAL PASIEN OSTEOARTHRITIS GENU - marli susanti; Sartoyo Sartoyo; Yohanes Deo Fau; Fransisca Xaveria Hargiani (Jurnal Kesehatan Hesti Wira Sakti, 2024)
Osteoarthritis is a disease that damages the knee joint due to aging and progressivity It affects two-thirds of humans over 65 years old. The physiotherapy treatment used is a combination of ultrasound and muscle energy technique with transcutaneous electrical nerve stimulation and muscle energy technique The purpose of this study was to determine the difference in the effectiveness of ultrasound diathermy and muscle energy technique with transcutaneous electrical nerve stimulation and muscle energy technique on changes in functional abilities of patients with genu osteoarthritis. The design of this study was quasi-experimental with a pre test post test with a study population consisting of 30 knee pain respondents at rsud dr.iskak tulungagung in july-september 2023, who met the inclusion criteria of 30 respondents with purposive sampling technique. Functional ability of genu osteoarthritis patients was measured by the womac scale before and after physiotherapy treatment, namely; giving ultrasound and muscle energy technique 15 respondents and transcutaneous electrical nerve stimulation and muscle energy technique 15 respondents every 2 times a week for 4 weeks.Using the Wilcoxon hypothesis test with the results of the median value of usd and met; pre value 65; post value 59; and P value 0.001, and median value of tens and met; pre value 61; post value 57; and P value 0.000. Shapiro-wilk comparison test sig value usd and met 0.271 > 0.05 means the data is normally distributed, sig value tens and met 0.802 > 0.05 means the data is normally distributed. Because the data is normally distributed, the statistical test to determine the treatment comparison, using the Independent Sample T Test p / sig value (2-tailed) 0.601> 0.05, conclusion: H0 accepted H1 rejected. So it can be concluded that there is no significant difference between the administration of usd and met with the administration of tens and met on changes in the functional abilities of patients with genu osteoarthritis.